Financial Reporting in North America. - Rivera, Juan M.; Boatsman, James R. (The Accounting Review, 1996)
Reviews the book `Financial Reporting in North America,' by the Canadian Institute of Chartered Accountants, Instituto Mexicano de Contadores, Financial Accounting Standards Board, assisted by KPMG Peat Marwick LLP.